TRANSIENT MODELING OF A SMALL HYDROKINETIC TURBINE - Vaz, J. R. P.; Moreira, T. H. S.; Brandão, D. T.; Lopes, J. J. A.; Figueiredo, S. W. O.; Mesquita, A. L. A.; Galhardo, M. A. B.; Blanco, C. J. C. (Revista de Engenharia Térmica, 2015)
In recent years, great attention has been given to the study of hydrokinetic turbines for power generation. Such importance is due to the use of clean energy technology by using renewable sources. Therefore, this work aims to present a relevant methodology for the efficient design of horizontal-axis hydrokinetic turbines with variable rotational speed. This methodology includes the Blade Element Method (BEM) for determining the turbine power coefficient, since BEM is widely used in the hydrokinetic turbine design due to its good agreement with experimental data. In addition, the dynamic equation of the driveline is used, taking into account the BEM to provide the rotor hydrodynamic torque coupled with the drive train model, including the multiplier and the electric generator. In this case, the modeling of the whole system comprises the hydrodynamic information of the rotor, the mass-moment of inertia, frictional losses and electromagnetic torque imposed by the generator. The theoretical results were obtained for the transient rotational speed and compared with field data measured from small hydrokinetic turbine installed at the Arapiranga-Açu creek, which is located in the city of Acará, Pará, Brazil.